Implementasi Logika Fuzzy pada Sistem Kecerdasan Buatan - Nasution, Helfi (Faculty of Engineering, Universitas Tanjungpura, 2012)
Abstract This paper is an explanation of fuzzy logic. Fuzzy logic have knew for long time and used in many fields by experts and engineers. In the beginning, fuzzy logic was used in some fields, only, like diseases diagnose system (in madicine); modelling of marketing system, operation riset (on economics); control of water quality, prediction of earthquake, classification and pattern recognition (in enginnering). Using of fuzzy logic in power system area have already done too, like probibility analysis, prediction and control of loads, identification of generator faults dan schedulling of generator maintenance. This paper is explained the application of fuzzy logic in the field of artificial intelligence. Keywords Fuzzy Logic, Artificial Intelligence